Probing the activity of eukaryotic rhomboid proteases in vitro - Cordier, Baptiste; Lemberg, Marius (Enzymology at the membrane interface - intramembrane proteases, 2017)
Proteolysis within the membrane is a recent concept in biology. Rhomboid intramembrane serine proteases are conserved in evolution and serve as key switches in diverse cellular pathways ranging from signaling to protein degradation. Since deregulation of intramembrane proteolysis can lead to severe diseases including neurodegenerative disorders, dissecting their enzymatic function and specificity becomes crucial. As membrane proteins, their solubilization, and purification are technically challenging. As a start point for a comprehensive in vitro characterization of eukaryotic rhomboid proteases, we depict in this chapter a robust workflow to find the best conditions to obtain pure and active enzymes from a bacterial expression system. To monitor the integrity of their active site and visualize substrate cleavage, various established activity assays including activity-based labeling and gel-based cleavage assays are described. These methods are illustrated by use of the Escherichia coli rhomboid protease GlpG and human RHBDL2 as an example.